Service Quality (Servqual) Toward Rawa Bebek’s Rusunawa Residents in Dki Jakarta - Retnowati WD Tuti (Jurnal Studi Pemerintahan)
Bukit Duri community relocation process and Fish Market to Rawa Bebek Rusunawa until now many problems arise. Resettled communities with forced then stay in Rusunawa was difficult to find a job to sustain life. Services pro- vided Rusunawa Rawa Bebek Unit business is still far from adequate. This issue is interesting to study. The purpose of this study was to analyze the quality of service to the residents of Rawa Bebek Rusunawa and find and implement a service model that is suitable for occupants Rusunawa. Knives analysis Rawa Bebek Rusunawa service quality using measures: 1). Convenience; 2). Reliability; 3) Personal Attention; 4). Citizen Influence; 5). Fairness; 6). Problem-Solving Approach; 7). Fiscal Responsibility, and 8). Security. While Methods used are Descriptive methods with a qualitative approach. Interviews conducted in data collection. Data Analysis Techniques 3 tolls are done using Data Analysis NVivo 12 plus consisting of Crosstab Query, Cluster Analysis, Matric Coding Query, and Clustered Similarity. Results and Findings, Ser- vice UPRS, or Jakarta to the residents of Rawa Bebek Rusunawa not good, which got only 17% of the ratings high. The second discovery, Model Service to Residents Rusunawa composed after Ratings Service Quality. Furthermore, the model applied to the services found doing Rusunawa Assistance to Resi- dents of Rawa Bebek. Bank organizations formed eight garbage; occupants have alternative sources of money quickly so that residents feel helpless. Also, there should be capacity building for employees UPRS. Then UPRS, Occupants Rusunawa, and researchers preparing the proposed changes to policies regarding tariffs and elimination of fines rent-subsidized apartment, urban transport through Rusunawa, structuring River East Flood Canal as a tourist attraction water delivered to the Department of Housing and Area Settle- ment of Jakarta as the direct supervisor UPRS. Excellent service for residents reached the Rusunawa.